Cutaneous manifestations in patients attending the hematology clinic at King Fahd Hospital of the University during a 13 week-period - Iqbal A. Bukhari; Osama Al Sultan; Abdulaziz Al Zahrani; Huda Alsuwaylih; Doaa Al Najim; Alla Altammar (Our Dermatology Online, 2015)
Background: Cutaneous disorders are common in patients with hematological diseases especially anemia. Dermatologists usually contribute to the management of these patients in parallel with other medical specialties. Aim: To report common dermatological problems in patients attending the hematology clinic at a secondary care hospital. Materials and Methods: The study was conducted at the hematology clinic of King Fahd Hospital of the University during a thirteen week period starting 17th of November, 2013 till 31st of January, 2014. All patients were fully examined and a consultative opinion was given to the attending hematologist. Data sheet was filled and analyzed by SPSS (Statistical Package for the Social Sciences) software version 17.0. Results: 138 patients were seen during the period of 13 weeks. There were 27 males and 111 females. Hemoglobin level was less than 10 gm/dl in 40.6% of patients. The most common reported cutaneous features were diffuse alopecia, hair thinning, pallor, pruritus, fragile skin, easy brusability, dry mouth and gum bleeding in descending frequency. Conclusion: Hematology patients suffered from variable dermatological disorders which suggest the importance of the initial dermatology consultation for those patients as part of their management plan.